Law and art: importance, relevance and challenges - Motta, Maiara; Cristina Canela, Kelly (Seven Editora, 2023)
Law and Art. can be connected in many different ways: as a constitutional right, as intellectual property rights, as well as reflected in other legal branches. This paper aims to analyze how these two subjects can be used in an interdisciplinary way, whether as methodological proposal in legal education, or as a toll to approximate this content to the population as a whole. Considering this is exploratory research, the man objectives are to contribute to Law and Art epistemological branch, as well as provide the initial contact with readers that might be interested by this interdisciplinarity. It is chosen as methodological instrument deductive reasoning in order to perform comprehensive-juridical research. The materials used are bibliographic and qualitative. Among the results, it can be noticed the relevance in this intersectional field, while also comprehending its origins, its relevancy and the main challenge it faces. DOI: 10.56238/pacfdnsv1-020